Antecedents of intention to adopt artificial intelligence services by consumers in personal financial investing. (10th May 2021) - Atwal, Glyn; Bryson, Douglas
Abstract: Antecedents of intention to adopt artificial intelligence and robo‐advisory services from the German private investors' perspective may guide future adoption behavior. This paper raises the question to what extent German investors' is willing to use robo‐advisory services instead of a human advisor to manage their investments. The exploratory study identified the following constructs that impact the intention to use artificial intelligence to invest: perceived risk, perceived usefulness, perceived ease of use, social influences, and intention to use. Findings from this study can help inform marketers when developing strategies to foster awareness and the adoption of robo‐advisors.